Analysis of Employee Productivity Incentives - Hart, Ludvík; Kalíšková, Klára; Chytilová, Helena; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2019)
In this master’s thesis I analyse employee incentive system of a Czech e-commerce company implemented in branch network of this company. This analysis is carried out in the context of agency theory, the principal-agent problem in particular. At first, I describe the economic theories that are the basis of this work. In particular these are the principal agent problem as described by Jensen and Meckling (1976), and incentive system design theories. The analysis is based on the economic model suggested by Baker, Gibbons and Murphy (1994). This model suggests a framework of the principal and agent behaviour in presence of contracts based on implicit and explicit contracts. To quantify my results I use a mathematical analysis based on input variable estimation and multiple regression analysis. I find that employees changed their behaviour after the introduction of the analysed incentive system in a predictive way. I could not however establish whether the goals the employer set out to achieve by this incentive system were met. I conclude that employees are responsive to the incentives, however more research needs to be done using multi-activity model specification to quantify the effect of this incentive system on employee behaviour more precisely.
Vedoucí práce: Klára Kalíšková
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2019
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2019
Způsob přístupu: Internet
Keywords: ekonomická analýza [obor dipl. práce]; diplomové práce; master's theses